A composition for wound healing - Mohamed, Suhaila; Roslan Tan, Rosalina; Ghasemi, Samaneh; Javadi, Mehdi; Manja, Maslia; Muhammad, Kharidah (2008)
A composition to be orally administered and/or topically applied for enhancing wound healing, tissue repair and cardiovascular health protection comprising an extract of vegetative parts of Ipomoea, Arecaceae plant family and/or seaweeds through extraction using alcoholic solvent with or without combination with a co-solvent, which may be aqueous or organic as an active ingredient.